An Analysis of Microplastics Contamination on Road Dust Around Jambi's Angso Duo Market - Lestari, Sri Indah; Ningsih, Syukrya; Marni, Lidia Gusfi (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
Road dust is a prevalent source of microplastics found in the atmosphere. The primary contributors to the presence of microplastics in dust are vehicle traffic, road surfaces, tire erosion, and road paint. The objective of this study is to categorize the various forms of microplastic pollution present in the road dust surrounding the Angso Duo Jambi market. The research employed a random sampling technique, specifically selecting 4 sample location locations. The total aggregation of microplastics amounted to 1.67 grams. Sample B exhibited the highest prevalence of microplastics, with a distribution of 2.78 grams in the vicinity to the right of Jambi's Angso Duo Market. The analysis of microplastics was conducted using a binocular microscope, Fourier Transform Infrared Spectroscopy (FTIR). The microscopic analysis of microplastic reveals the presence of several forms, namely fibres, fragments, and films. The FTIR study results indicate that polyethylene is the prevailing polymer type. The chemical composition and types of microplastic polymers found near the Angso Duo Jambi market, as determined by the results collected, include polyethylene, polypropylene, and polystyrene. The environmental impact of microplastics is intricately linked to the characteristics of the microplastics themselves, including their kind, size, concentration, and duration of exposure. Further investigation is required to examine the enduring consequences of microplastics on the environment, particularly in relation to the contamination of road dust.